1998
DOI: 10.2151/jmsj1965.76.3_403
|View full text |Cite
|
Sign up to set email alerts
|

General Aspects of Land and Sea Breezes in Western Seto Inland Sea and Surrounding Areas

Abstract: The general aspects of land and sea breezes in western Seto Inland Sea and the surrounding areas are revealed from an analysis of the wind data obtained from the AMeDAS. The study area consists of Kyushu, the western part of Chugoku, and the western end of Shikoku surrounded by the Pacific Ocean, the East China Sea and the Sea of Japan, and the study area contains inland seas both wide and narrow.The day of the land and sea breeze in the study area is specified from the day when the land and sea breeze appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The PW is important in determining whether or not a sea breeze will be detectable on land (a very strong offshore PW will prevent the SBC from reaching the coast), as well as exerting an influence on its behavior [e.g., Finkele et al ., 1995]. Mizuma 's [1995, 1998] observational studies of SBC behavior on the coast of Japan include descriptions of several manually identified sea breeze modes, which are dependent on the shape of the local coastline and the direction and strength of the PW. Several other studies have examined SBC response to the PW both generically and along specific coastlines [e.g., Fisher , 1960; Estoque , 1962; Pearson et al ., 1983; McKendry and Roulet , 1994; Planchon and Cautenet , 1997; Melas et al ., 1998; Asimakopoulos et al ., 1999; Clappier et al ., 2000; Melas et al ., 2000; Laird and Kristovich , 2001; Oliphant et al ., 2001; Lericos et al ., 2002].…”
Section: Modern Understandingmentioning
confidence: 99%
“…The PW is important in determining whether or not a sea breeze will be detectable on land (a very strong offshore PW will prevent the SBC from reaching the coast), as well as exerting an influence on its behavior [e.g., Finkele et al ., 1995]. Mizuma 's [1995, 1998] observational studies of SBC behavior on the coast of Japan include descriptions of several manually identified sea breeze modes, which are dependent on the shape of the local coastline and the direction and strength of the PW. Several other studies have examined SBC response to the PW both generically and along specific coastlines [e.g., Fisher , 1960; Estoque , 1962; Pearson et al ., 1983; McKendry and Roulet , 1994; Planchon and Cautenet , 1997; Melas et al ., 1998; Asimakopoulos et al ., 1999; Clappier et al ., 2000; Melas et al ., 2000; Laird and Kristovich , 2001; Oliphant et al ., 2001; Lericos et al ., 2002].…”
Section: Modern Understandingmentioning
confidence: 99%
“…However, wind data collected at these stations clearly showed a wind direction shift between day and night, indicating the land-sea breeze phenomenon in the Wakasa Bay area. As indicated by Mizuma (1995;1998) for Osaka Bay and western Seto inland sea, although the land-sea temperature contrast appears small for generating a strong circulation, the combined effects of mountain winds caused by the geographic feature of Wakasa Bay surrounded by mountainous areas could have induced land-sea circulation. During nighttime (until early morning), winds blow from the land (mountain side) to the sea.…”
Section: Possible Causes Of the Diurnal Cyclementioning
confidence: 99%
“…Diurnal variations in ground temperature, static stability, Coriolis force, prevailing wind, and topography including the size and shape of land and coastline also affect the development of sea/land breeze (Simpson 1994). Mizuma (1995Mizuma ( , 1998 has described the sea/land-breeze system in the Seto Inland Sea, but did not pay attention to either the spatial structure of the sea/land breeze offshore or the influence of the SST front on the sea/land-breeze system in the Seto Inland Sea.…”
Section: Introductionmentioning
confidence: 99%